2017
DOI: 10.7716/aem.v6i1.469
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Dual-Mode Microstrip Bandpass Filters Using Triangular Patch Resonators

Abstract: In this paper, highly selective dual-mode microstrip bandpass filters are proposed using horizontal and vertical slots formed on the surface of a triangular patch. Slots are responsible for splitting and coupling of dual degenerate modes and also facilitate in controlling their resonant frequencies by varying the dimensions of the slots. Horizontal and vertical slots reroute the direction of the flow of current on the surface of the patch, which results in switching of transmission zeros. Two 2-pole and one 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A discontinuity in a microstrip is caused by an abrupt change in the geometry of the strip conductor, and electric and magnetic field distributions are it can be observed that the bandwidth and the position of the transmission zeros are also varied [24]. It can be seen that, when the impedance values are increased, the bandwidth will become wider and vice versa.…”
Section: Circuit Diagram Of Hybrid Ring Resonatormentioning
confidence: 99%
“…A discontinuity in a microstrip is caused by an abrupt change in the geometry of the strip conductor, and electric and magnetic field distributions are it can be observed that the bandwidth and the position of the transmission zeros are also varied [24]. It can be seen that, when the impedance values are increased, the bandwidth will become wider and vice versa.…”
Section: Circuit Diagram Of Hybrid Ring Resonatormentioning
confidence: 99%
“…The dual-mode BPFs in [1][2][3] have been designed using closed loop, meandered dual-mode resonators like octagonal, hexagonal, star shaped resonators. The triangular, square patch resonators with corner cuts [4], [5] have also been proposed to design dual-mode BPFs. However all these reported filters have narrow bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…Since these filters are cost effective and easily fabricated by Printed circuit Board Technology (PCB) they have gathered more attention in satellite and mobile communications. In literature, Star shaped resonator with triangular perturbation, triangular patch with vertical and horizontal slots, symmetrical fractal structure etched on meander loop resonator have been proposed to design Dual-Mode filters [1][2][3]. Parallel coupled stepped impedance resonator with proper tapping at input and output resonators has been proposed [4] and tunable transmission zeros in stopband have been achieved with tapping at input and output.…”
Section: Introductionmentioning
confidence: 99%